Prevalence of HIV and Associated Risks of Sex Work among Youth in the Slums of Kampala - Swahn, Monica H. (AIDS Res Treat, 2016)
Purpose. The purpose of this study is to examine the prevalence of and risk factors for engaging in sex work among youth living in Kampala, Uganda. Methods. Analyses are based on a cross-sectional study (N = 1,134) of youth aged 12-18 years, living in the slums of Kampala, conducted in Spring of 2014. The analytic sample consisted of only sexually active youth (n = 590). Youth who reported engaging in sex work were compared to youth who did not report sex work. Multivariable analyses were conducted to examine factors associated with sex work. Results. Among the youth who had ever had sexual intercourse (n = 590), 13.7% (n = 81) reported engaging in sex work. Self-reported HIV prevalence was 13.9% among the total sample (n = 81) and 22.5% (n = 18) among youth engaged in sex work. Engaging in sex work was associated with being female (AOR 10.4; 95% CI: 3.9, 27.4), being an orphan (AOR 3.8; 95% CI: 1.7, 8.4), ever drinking alcohol (AOR 8.3; 95% CI 3.7, 19.0), and experiencing any rape (AOR 5.3; 95% CI: 2.9, 9.5). Discussion. The reported prevalence of sex work is high among youth in the slums of Kampala and is associated with high HIV prevalence, ever drinking alcohol, previously being raped, and being an orphan.